The Experience Sampling Method in Monitoring Social Interactions Among Children and Adolescents in School: A Systematic Literature Review - Mölsä, Martina E.; Lax, Mikael; Korhonen, Johan; Gumpel, Thomas P.; Söderberg, Patrik (Frontiers in Psychology, 2022)
The experience sampling method (ESM) is an increasingly popular data collection method to assess interpersonal dynamics in everyday life and emotions contextualized in real-world settings. As primary advantages of ESM sampling strategies include minimization of memory biases, maximization of ecological validity, and hypothesis testing at the between- and within-person levels, ESM is suggested to be appropriate for studying the daily lives of educational actors. However, ESM appears to be underutilized in education research. We, thus, aimed to systematically evaluate the methodological characteristics and quality of published ESM studies of social interactions among children and adolescents in school settings, as well as to explore how much variance in social interaction variables could be attributed to the within-person level. Using Academic Search Complete, APA PsycINFO, APA PsycArticles, ProQuest, Web of Science, Wiley Online Library, and SAGE Journals, and in accordance with PRISMA guidelines and pre-defined eligibility criteria, we conducted a systematic literature search of experience sampling studies up to November 2020. To assess methodological quality, we used a modified checklist for reporting of ESM studies. Of the originally 2 413 identified studies, a final 52 experience sampling studies were included in the present review. Findings on study design characteristics generally revealed wide variability. Even if high-quality studies were associated with higher scores on training of participants in using the ESM procedure, and use of incentives, these design strategies did not reveal a statistically significant impact on compliance. The intraclass correlation coefficient was reported in nine studies and on average 58% of the variance in social interaction variables could be attributed to within-person fluctuation between timepoints. The current study is the first to systematically review ESM-based studies on social interactions among children and adolescents in the school context. These observations suggest that ESM is a potentially favorable technique for extracting complex social phenomena in real-world settings. We hope that this review will contribute to improving the quality assessment of ESM studies as well as to inform and guide future experience sampling studies, particularly regarding social phenomena with children and adolescents in educational settings.